Halvledarbristens effekt på en svensk biltillverkare och företagets strategiska initiativ under situationen - Storsletten, Fabian; Nilsson, Jesper (My University, 2023)
During the pandemic, an already existing global shortage issue of semiconductor components was brought to attention. There are several different reasons for the emergence of this shortage, but the negative consequences are even more pronounced. The purpose of this study is to examine its impact on the Swedish automotive industry and identify strategies that the car manufacturer has applied. To gain a deeper understanding of the semiconductor industry, a thorough analysis of historical events and how the supply chain functions was conducted. To further enhance the understanding, two in-depth interviews were conducted with individuals working with this issue on a daily basis within the Swedish automotive industry. One observation was that the component shortage is a central reason for a conservative state of innovation and, more specifically, in electrification. After an examination of the aforementioned aspects, we were able to systematically identify the consequences faced by the car producer, including production bottlenecks, increased material costs, and longer lead times. The company has strategically worked to keep the shortage under control by aiming for improved communication and better relationships with subcontractors, compromising on the product mix, as well as financial management, and ultimately self-procuring semiconductors to keep production rolling. In summary, the report illustrates the challenges the Swedish automotive industry is undergoing due to the shortage. It becomes evident that this shortage impacts the entire supply chain and manifests gradually throughout the supplier network. The work provides an overview of the impact of the semiconductor shortage on the Swedish automotive industry. By understanding how it affects the logistics networks and analyzing strategies to adapt, car companies can make informed decisions to manage the situation and ensure continued success in a challenging market.
Keywords: Halvledarindustrin; svenskbilindustri; Försörjningsstörningar; Pandemin; Spotmarknaden; komponentunderskott; Semiconductor industry; Swedish Automotive industry; Supply disruptions; Pandemic; Spot market; Component deficit